Unnatural Frenchmen : The Politics of Priestly Celibacy and Marriage, 1720-1815 - Cage, E. Claire, 1982- (Book collections on Project MUSE., 2015)
This book examines the divisive issue of clerical celibacy in Enlightenment and revolutionary France, looking at how it shaped religious politics, the lived experience of French clerics, and gendered citizenship. Drawing on a wide base of printed and archival material, including thousands of letters that married priests wrote to the Pope, historian Claire Cage highlights individual as well as ideological struggles.